1994
DOI: 10.1099/0022-1317-75-5-1189
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Bovine Viral Diarrhoea Virus p80 Protein in Subpopulations of Bovine Leukocytes

Abstract: Flow cytometry and two-colour immunofluorescence were used to detect cytoplasmic bovine viral diarrhoea virus (BVDV) antigen in ieukocytes from viraemic cattle. Monoclonal antibody to the p80 protein of BVDV, a non-structural viral antigen, was used to identify the subpopulations of leukocytes in which viral protein synthesis had occurred. Viral antigen was detected in 23 % of peripheral blood mononuclear cells. Monocytes were found to have the highest frequency of infection (35 %). A higher proportion ofCD2 +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 18 publications
2
24
0
1
Order By: Relevance
“…Chi et al (61) and others (54,56,62) showed that IFN-a and IFN-l together mediated the CD4 + T cell suppression seen during respiratory syncytial virus infection to both virus and recall responses to a third-party Ag. During BVDV infection in vivo, only a small percentage of DCs are infected (63). However, activation/maturation may be induced in uninfected immature myeloid DCs following exposure to IFN produced by pDCs.…”
Section: Discussionmentioning
confidence: 99%
“…Chi et al (61) and others (54,56,62) showed that IFN-a and IFN-l together mediated the CD4 + T cell suppression seen during respiratory syncytial virus infection to both virus and recall responses to a third-party Ag. During BVDV infection in vivo, only a small percentage of DCs are infected (63). However, activation/maturation may be induced in uninfected immature myeloid DCs following exposure to IFN produced by pDCs.…”
Section: Discussionmentioning
confidence: 99%
“…BVDV is known to infect cells of the innate immune system, including monocytes, macrophages, and dendritic cells. 36 Recent studies have demonstrated that BVDV-infected monocyte-derived macrophages have significantly impaired functional capacity, as measured by phagocytosis and cytokine production in vitro. 7,29 Because macrophages and osteoclasts originate from a common precursor cell, both cell types may be affected by a similar mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…For negative sorting to obtain gd T cells, a cocktail of mAb IL-A12 [42] for CD4, mAb MCA837G (Serotec, Oxford, UK) for CD8, mAb IL-A58 [43] for IgM, and mAb IL-A15 [44] for CD11b was used. Cells were then incubated with goat anti-mouse IgG-conjugated magnetic microbeads (Miltenyi Biotec, Auburn, CA, USA) at 41C for 20 min.…”
Section: Animals and Lymphocytesmentioning
confidence: 99%